Analysis of Reference Group and Opinion Leader Towards Interest In Buying Yoghurt - Goncalves, Manuel; Sutanto, Jushua Putra (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
The research aims to find out analysis of reference group and opinion leader towards interest inbuying yogurt The purpose of this study was to determine the significance of reference groups and opinion leaders on the purchase interest of Yogurt. Yogurt is a start-up company managed as an entrepreneurship business project. Yogurt experienced a decline in sales which could be caused by unexpected factors, the loss of cooperation contracts with other companies, and the lack of appropriate strategies in promotion. Design. Methodology/ approach. Based on a review of the literature and the number of samples used was 124 respondents. The research approach was carried out quantitatively using processed using SPSS version 25 programs. The data collection method uses an instrument research based on variables which are expected significantly influence consumer buying interest. Originality/value – These results of research showed that the reference group and opinion leader variables significantly influenced the purchase interest of Yogurt.